Improvement of the scintillation properties of Gd3Ga3Al2O12:Ce, B single crystals having tailored defect structure. Issue 9 (7th August 2015) - Tyagi, M.; Singh, A. K.; Singh, S. G.; Desai, D. G.; Patra, G. D.; Sen, S.; Gadkari, S. C.
<x xml:space="preserve">Abstract</x> A novel approach is reported to minimize various defect centers in Ce doped Gd3Ga3Al2O12 single crystals to improve the scintillation properties. The crystals of Gd3Ga3Al2O12 codoped with 0.2 at% Ce and B (GGAG:Ce, B) have been grown in air and argon ambient using the Czochralski technique. The scintillation light output of crystals grown in Ar ambient was significantly increased after annealing the crystals in air. The measured light output of 60000 ph/MeV for annealed crystals is the highest value reported among this class of materials. As a consequence, the energy resolution at 662 keV gamma‐rays from a 137Cs source was improved from 8% for the crystals grown in air to 6% for crystals grown in Ar and subsequently annealed in air. Further, the thermal quenching energy of photoluminescence (PL) emission was increased to be 470 meV for the annealed crystals. The thermoluminescence (TL) measurements suggest that the crystals grown in Ar ambient and post‐growth annealed in air may have a lesser concentration of trap centers which subsequently lead to the improvement in optical and scintillation properties leading to a superior detector performance. (© 2015 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim)